Monstrous Origins: Atwood, Pachter, and Anansi’s Speeches for Doctor Frankenstein - Sugars, Cynthia (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2025)
In 1966, Margaret Atwood and her long-time artist friend Charles Pachter produced a handmade collaborative text entitled Speeches for Doctor Frankenstein. The book is a series of poems by Atwood, spoken through the imagined voice of Doctor Frankenstein about the perils of creation, and was illustrated with Pachter’s evocative woodcuts. Only 15 copies of the work were produced. In 2012, Anansi Press issued an eBook version to coincide with the 40th anniversary of Atwood’s well-known guidebook to Canadian literature, Survival. The eBook of Speeches was promoted by Anansi, not only as an act of Frankensteinian creation (the physical book was literally hand-sewn and put together from bits and pieces, including human hair), but also as a work that distilled the “Gothic origins” of Canadian literature. The marketing of the eBook turned Canadian literature into a Gothic monster, taking readers back to the moment when, according to their promotional video, “a piece of Canadian cultural history is created,” here packaged for resale as a virtual and elusive cultural artifact. By launching the two works in tandem – Survival and Speeches – Anansi led readers to consider the ways that Canadian literature in 2012 was itself a monster looking back to the (textual) origins of its birth and survival.